Customary arbitration as a tool for ensuring access to justice for women in Nigeria: a case study of the women’s law clinic, faculty of law, University of Ibadan (2017)
Using the Women’s Law Clinic, Faculty Law, University of Ibadan, Nigeria, as a case study, this paper examines the use of customary arbitration as a tool for ensuring access to justice. Further, the paper examines the need to have a remedial system of resolving disputes for the good of the society. The remedial system of law is referred to as customary arbitration. The paper identifies the challenges facing access to justice and advances the argument on the perception of access to justice as a human right, as well as the need to promote access to justice especially where people are disadvantaged. The papers concludes examining the effectiveness of customary arbitration in Nigerian community and its applicability as a tool in ensuring access to justice